Macrophage heterogeneity in atherosclerotic plaques - Johnson, Jason L. (2009)
PURPOSE OF REVIEW: The varied behaviour of macrophages and foam cells during atherosclerosis and its clinical sequelae prompt the question whether all these activities can be the property of a single cell population. RECENT FINDINGS: Subsets of monocytes with distinct patterns of surface markers and behaviours during inflammation have recently been characterized and shown to have complementary roles during progression of atherosclerosis. A variety of macrophage phenotypes derived from these monocyte subsets in response to mediators of innate and acquired immunity have also been found in plaques. Based on functional properties and genomic signatures, they may have different impacts on facets of plaque development, including fibrous cap and lipid core formation. SUMMARY: Monocyte and macrophage phenotypic diversity is important in atherogenesis. More work is needed to define consistent marker sets for the different foam cell phenotypes in experimental animals and humans. Cell tracking studies are needed to establish their relationship with monocyte subtypes. In addition, genetic and pharmacological manipulation of phenotypes will be useful to define their functions and exploit the resulting therapeutic potential.